The relationship between resilience, anxiety, and depression in Chinese collegiate athletes - Lyu, Chengjie; Ma, Rong; Hager, Ronald; Porter, Dave (Frontiers in Psychology, 2022)
Anxiety disorder is becoming increasingly prevalent across college campuses, particularly among collegiate athletes who face different stressors and challenges than their non-athlete peers. Anxiety and depression are well documented comorbidities. Furthermore, the number of Chinese collegiate athletes suffering from anxiety and depression is increasing. Psychologists have recently begun to take a more prophylactic approach to defend against these disorders through resilience education. Resilience education focuses on developing greater capacity to cope when mental and emotional challenges arise. The purpose of this study was to analyze the relationship between resilience, depression, and anxiety in Chinese collegiate athletes. This study provides additional evidence of the value of incorporating an effective resilience educational module amongst collegiate athletes. Research design The study employed a survey research design to explore the complex relationship between depression, anxiety, and resilience for collegiate student athletes. Data analysis strategy Structural Equation Modeling (SEM) was employed to account for any measurement error between the observed items (responses on the instruments) and the latent variables (anxiety, depression, and resilience). The theoretical hypothesized relationship for this study is an inverse relationship between anxiety and depression, on the one hand, and resilience on the other hand. The SEM statistical analysis from this study supported this theoretical model. Effective sample size 599 collegiate athletes from six different universities in the province of Guangdong, China P.R. participated in this study.